Kontribusi Hara Sulfur terhadap Produktivitas Padi dan Emisi Gas Rumah Kaca di Lahan Sawah - A. Wihardjaka; Poniman Poniman (Iptek Tanaman Pangan, 2015)
National food demand, especially rice increases in accordance with the rate of population growth. The availability of rice mostly is still relying on the intensification of irrigated and rainfed lowlands, through applying balance nutrients fertilization, including the management of sulfur (S). Sulfur as one of the essential nutrients, is required for protein and enzyme syntheses, amino acids formation and metabolic acticities in plants. However, the program of rice production increases is also impacting on the increase of atmospheric greenhouse gases. The objective of this paper was to discuss sulfur management on rice production system and its impact on greenhouse gas emissions in lowland rice areas in Indonesia. Sulfur fertilization of 20 kg S/ha along with the application of N, P, K fertilizers was considered adequate to provide better plant growth and to yield of 5 t grains/ha. Sulfur fertilization should be applied before active tillering phase by broadcasting on the surface of flooded lowland rice field to obtain higher efficiency of S fertilizer. Besides increasing crop yield, sulfuric fertilization on rice crop played a role in mitigating greenhouse gases emission. The sulfuric fertilizer application reduced atmospheric greenhouse gases (GHGs) release, especially CH4 and N2O from lowland rice. Balance sulfur fertilization could improve yield and grain quality of rice as well as mitigated greenhouse gas emissions from the lowland rice areas.